Kinerja guru SMPN 2 Ungaran tahun 2022 sebagai pengaruh dari pengalaman kerja motivasi berprestasi dan supervisi kepala sekolah - Welius Purbonuswaanto (Universitas Sebelas Maret, 2022)
This research journal aims to determine: the effect of work experience, achievement motivation and supervision of the principal on the performance of SMPN 2 Ungaran teachers in 2022. Specifically, this study aims to analyze (1) The effect of work experience on the performance of SMPN 2 Ungaran teachers in 2022. (2) The effect of achievement motivation on the performance of SMPN 2 Ungaran teachers in 2022. (3) The effect of the Principal's supervision on the performance of SMPN 2 Ungaran teachers in 2022. This type of research is quantitative. The population in this study were all 156 teachers at SMPN 2 Ungaran. Data collection technique with a questionnaire. The results of this study indicate that: (1) There is a positive and significant influence together of work experience, achievement motivation and principal supervision on the performance of junior high school teachers in Ungaran. This means that the longer teaching, increased motivation for achievement and frequent principals, the better the teacher's performance. Vice versa, if there is little work experience, low achievement motivation, and rarely supervised by the Principal, then the performance produced by the teacher is also low. (2) There is a positive and significant influence between work experience on teacher performance. (3) There is a positive and very significant effect of achievement motivation on teacher performance. (4) There is a positive and significant influence between the Principal's supervision on teacher performance. Of the three independent variables, the dominant influence on teacher performance is the work experience aspect.